The Relationship Between Aerobic Physical Exercise to Functional Capacity in Heart Failure Patients at Haji Adam Malik General Hospital Medan - Khairunnisah, Dina; Hasan, Harris; Reynaldo, Abdul Halim; Haykal, Teuku Bob; Sarastri, Yuke (Journal of Society Medicine, 2023)
Introduction: The prevalence of heart failure is known to increase day by day, as well as the incidence of rehospitalization and death. One way that can be done is to optimize health status and perform cardiac rehabilitation. Aerobic exercise is recommended for patients with heart failure. Aerobic exercise has been shown to increase functional capacity in patient with heart failure. The aim of this study is to assess the relationship between aerobic exercise with functional capacity improvement in patient with heart failure in Haji Adam Malik General Hospital, Medan. Method: This study was conducted using prospective cohort method on 35 patients with heart failure in a cardiac rehabilitation program at Haji Adam Malik General Hospital, Medan. Functional capacity and 6-Minute Walk Test (6MWT) data were collected before and after aerobic exercise. Univariate and bivariate data analysis were performed using SPSS. Results: 35 samples were included in this study, with an average age of 54,57±1,28 years and dominated by male. The result showed an increase in distance after aerobic exercise program compared to the initial examination (373,6±133,64 vs 192,57±64,68) with p-value <0,001. There was an increase in functional capacity from 3,55±1,12 MET to 6,6±2,44 MET after aerobic exercise (P<0,001). Conclusion: There is a significant relationship between aerobic exercise and functional capacity improvement in patients with heart failure at Haji Adam Malik General Hospital, Medan.